NIMG-66. LONG-TERM FOLLOW-UP OF NEUROFIBROMATOSIS TYPE 1 PATIENTS USING WHOLE-BODY MRI DEMONSTRATES DYNAMIC CHANGES IN INTERNAL NEUROFIBROMA SIZE. (11th November 2019) - Ly, Ina; Thalheimer, Raquel; Cai, Wenli; Bredella, Miriam; Merker, Vanessa; Plotkin, Scott; Jordan, Justin
Abstract: BACKGROUND: Neurofibromas affect 40–50% of neurofibromatosis type 1 (NF1) patients and can cause significant morbidity and mortality. They grow more rapidly during childhood and adolescence but studies in adults are limited by their retrospective nature and follow-up time < 3 years. The long-term natural history of neurofibromas remains unknown. No guidelines exist on the need and frequency of surveillance imaging for patients. Whole-body MRI (WBMRI) can detect whole-body tumor burden, including internal neurofibromas. METHODS: 17 adult NF1 patients who underwent WBMRI between 2007–2010 (Scan 1) underwent repeat WBMRI between 2018–2019 (Scan 2). Internal neurofibromas were segmented on short tau inversion recovery (STIR) sequences and tumor volume was calculated using a computerized volumetry and three-dimensional segmentation software. Circumscribed tumors were defined as discrete; invasive tumors or those involving multiple nerves were defined as plexiform. Tumor growth and shrinkage were defined as volume change ≥ 20% over the entire study period. RESULTS: Median patient age was 43 years during Scan 1 and 53 years during Scan 2. Median time between Scan 1 and 2 was 9 years. A total of 140 neurofibromas were assessed. 24% of tumors grew by a median 63% (6.8% per year). 54% of tumors spontaneously decreased in volume by a median 60% (7% per year) without treatment. On a per-patient basis, 18% of patients had overall tumor growth and 41% overall tumor shrinkage. 8 new tumors developed in 7 patients. 16 tumors resolved entirely without medical or surgical intervention. Growth behavior did not correlate with discrete or plexiform morphology. CONCLUSION: A subset of internal neurofibromas in adult NF1 patients grow significantly over a long-term period, suggesting that continued monitoring of these patients may be warranted. Surprisingly, more than half of neurofibromas shrink spontaneously without intervention. Continued patient enrollment and correlation of imaging findings with functional outcomes are underway.